‘Entre la hoz y el martillo’: vínculos entre música culta, folklore y política en Chile durante la Guerra Fría (1947-1973) - Mauricio Gómez Gálvez; Javier Rodríguez Aedo (Les Cahiers ALHIM)
This article analyses some aspects of Chilean musical history during the Cold War, and more precisely, the impact that the aesthetic theories originated in the USSR had on local communist musicians. Through the study of diverse sources, some used for the first time, we try to show how these ideas circulated, who received them and how they were reinterpreted. The article argues that the media linked to the Chilean Communist Party were key in defining the social role of art, and often locally echoed debates originally developed in the Soviet Union. Between the autonomy inherent to the artistic vocation and the heteronomy due to their ideology, Communist musicians explored different solutions, more or less original, in order to shape their own model of expression of their political commitment.